(3EOGQI GdehGQO GdHTQjI GdOhdjI (B/s - (3YHGS, Ydjs ((3YeGf(B: s (3GKQGA ddfTQ(B, s, 2008)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3GdCYeGd GdOhdjI acQI YGeI Mhd eaghegG(B-(3HjFJgG(B-(3JfXjegG,EOGQI GdehGQO GdHTQjI GdOhdjI,GdbjGOI h GdSdhc GdaQOj aj GdCYeGd GdOhdjI,Jchjf GdeOQGA GdOhdjjf,GdYdGbGJ GdSdhcjI ddCaQGO h GdefXeGJ aj GdCYeGd GdOhdjI,GdehGQO GdHTQjI GdOhdjI h GdJHGjfGJ GdKbGajI, GdJYhjVGJ aj GdCYeGd GdOhdjI,GdJOQjH h GdJWhjQ GdOhdj,GdJchjf GdCNdGbj ddehGQO GdHTQjI GdOhdjI, GdMdbGJ GdOQGSjI(B.s
(3HjHdjhZQGajG(B: (3U(B.465s
Keywords: (3EOGQI GdCaQGOs; (3GdehXahfs; (3ehGQO HTQjIs